Analisis Produktivitas Flange Menggunakan Metode Objective Matrix (OMAX) dan Fault Tree Analysis (FTA) - Rahmasari, Venny; Nugroho, Andung Jati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
PT Mitra Rekatama Mandiri is a metal casting company that produces flange (sand pump machine axis cover). Based on company data for 2023, flange production results experienced ups and downs with a total production output of 303,946 kg. The aim of the research’ is to determined the level of productivity, analyze the factors that influence the level of productivity and provide suggestions for improvement. The methods used are (OMAX) and (FTA). The results of productivity measurements show that production is unstable with an increase in extreme productivity levels in August 2023 of 690 and October 2023 of 711 as well as a decrease in extreme productivity levels in June 2023 of -27, September 2023 of -27 and November 2023 of -15. Factors that influence productivity levels are unscheduled machine maintenance, old machine components, machine capacity exceeding 500 kg, erosion of furnace linings, dirty machines, melting temperatures exceeding 1,200°C, hot environmental conditions and poor lighting. Proposed improvements include making a machine maintenance schedule, replacing machine components, checking the machine capacity does not exceed 500 kg, replacing the furnace lining material, cleaning the machine, checking the melting temperature, making ventilation and adding lighting.